The impact of film audio description style on presence in Chinese visually impaired audiences - Yang, Hui; Xie, Danni; Li, Yutao (Frontiers in Psychology, 2025)
This study investigates the impact of film audio description (AD) styles on dimensions of presence—spatial presence, engagement, ecological validity, and negative effects—among visually impaired audiences in China. Two distinct styles of AD were evaluated: objective AD and subjective AD. Using a mixed-methods methodology that integrated quantitative surveys with qualitative focus group discussions, the study examined participants’ emotional and perceptual responses. The findings indicated that the subjective AD style significantly enhanced key dimensions of presence, including greater engagement, improved spatial awareness, and increased ecological validity while reducing confusion compared to the objective style. These effects were consistent across participants with varying levels of visual impairment and educational backgrounds, demonstrating the broad applicability of the subjective AD style. The study underscores the potential of subjective AD to enhance immersion and elevate the viewing experience, contributing to more inclusive and effective media accessibility for visually impaired audiences.